Comparative Analysis of Customer Satisfaction towards Islamic and conventional banking: An empirical Study from Saudi Arabia. - Fayaz Ahmad Lone; Ebraheem Mohamad Aldawood; Ulfat Rashid Bhat (International Review of Management and Marketing, 2017)
Islamic banking is gradually emerging everywhere in the world. Half a century ago, Islamic banking was just a concept contained in books only, but today it is a success story not only in Muslim countries of Middle East but even in the UK and the USA. As customer satisfaction is the compulsory element of every kind of business so Islamic banking also has to pay more attention towards customer satisfaction. Modern banking system of Saudi Arabia is unique due to political and technological environment of this country. Both conventional and Islamic banks are working together in this country to maximize the customer satisfaction and profit margin. Customers have a choice to switch either type of banking (Islamic to conventional or conventional to Islamic); this has created a challenge for banks. To retain and attract the customers, banks have to adopt different services and strategies. In the present study, the level of customer satisfaction in both conventional and Islamic banks is measured through comparative study. Data were collected through a well-designed questionnaire on Likert's five point scale from both Islamic and conventional banks of Saudi Arabia. Data were collected from four regions (Riyadh, Dammam, Makkah and Madinah) with the intention to represent the whole Saudi Arabia.  After using independent samples t-test and one way ANOVA, it has been found that customers are equally satisfied with both types of banks and also no difference of customer satisfaction was found from different regions. This is a good sign for Islamic banking as it is competing with a conventional banking system which has its long history. At the end suggestions for developing Islamic banking in Saudi Arabia were presented.